Labor Dispute, Alternative Resolution, and Its Costs (Journal of Universal Excellence, 2026)
Research Question (RQ): Do Slovenian courts have sufficient public funds available to ensure the smooth implementation of alternative dispute resolution methods?Purpose: The purpose of the research is to present labor disputes and their alternative resolution methods within the judicial system, with a focus on mediation as a mandatory procedure under the ZARSS. The research focuses on the costs incurred by courts in implementing these alternative procedures.Method: During the research, social science research methods were used. The research began with the collection method, through which the existing literature was reviewed. Subsequently, the historical method was used for a brief presentation of ZARSS, and the descriptive analysis method was used to examine the legal bases and professional literature. Quotes of authors’ opinions were treated within the compilation method. For the presentation of costs incurred for the implementation of alternative dispute resolution methods from 2018 to 2023, the data analysis method was used. Based on the analysis of statistical data as a whole, the forecasting method was used, and to some extent, the inductive and deductive methods as well.Results: Sufficient funds are available for the implementation of ADR. They are mainly provided within the framework of European cohesion policy and are used for the promotion of ADR, while also facilitating easier access to ADR for parties, especially in civil and labor disputes.Organization: The research offers useful findings for managers of judicial institutions. By emphasizing cost analysis, it enables more efficient planning of financial and human resources and improves procedures to reduce court backlogs.Society: The research highlights the importance of access to legal protection, emphasizing the need for sustainable financing of ADR, which reduces costs and time for parties in labor disputes. By promoting ADR among the general public, it contributes to greater use of mediation, reducing conflict situations and strengthening a culture of dialogue. At the societal level, the research encourages the responsible use of public funds and the long-term improvement of the judicial system.Originality: The originality of the research is reflected in the consideration of financial and organizational aspects of ADR in the context of the Slovenian judiciary, which is a new approach in the existing literature. The combination of legal, economic, and statistical analysis offers a comprehensive insight into the functioning of ADR and reveals previously overlooked levers for improvements. The findings of the research are not only theoretical but also practical, providing concrete solutions for improving the accessibility and efficiency of ADR.Limitations/Future Research: The research focuses on the Slovenian legal system and a specific period (2018–2023), which may limit the general applicability of the findings. Future research could compare the functioning of ADR in different countries or legal systems and analyze the long-term effects of sustainable financing of ADR on society and judicial procedures. Additionally, it would be worthwhile to investigate the impact of digitalization on the implementation of ADR.
Keywords: labor dispute; alternative dispute resolution; costs of alternative dispute resolution